CURVE OF GROWTH AND UPTAKE FOR THE GARLIC CROP UNDER FIELD CONDITIONS - ANDRIOLI, Fabrícia Flávia; PRADO, Renato de Mello; ANDRIOLI, Itamar; SAES, Ligia Pecoriello (Scientia Agraria, 2008)
The knowledge of the nutrients uptake for the garlic crop in field conditions is important for the adequate handling of the fertilization of the culture. Thus, the work was objectified to evaluate the curve of growth and the nutrients uptake for the of the garlic, cv. Roxo Pérola de Caçador, gotten way culture of meristema it exempts of virus. The experiment was arranged in a completely randomized design with three replications. Six collections of plants of garlic, cultivated in field conditions had been used, in the city of Pitangueiras-SP. In the collections, it was evaluated production of dry mass of root, leaf and bulbs of the plants and the accumulation of nutrients, to each 15 days, initiating to the 30 days up to 105 days after the plantation (DAP). The plantation after had a predominance in the accumulation of dry leaf mass during 75 days and after that in the end of the cycle the accumulation of dry mass of bulbs even predominated. The garlic crop after presented the maximum absorption of the nutrients in the period of 75 the 90 DAP, except the P, Ca and Zn that greater had after absorption this period. The nutricional requirement of the garlic crop, obeyed the following decreasing order: N, K, Ca, P, S, Mg, Fe, Zn, Mn, B and Cu.